2006
DOI: 10.1210/me.2005-0171
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Partial Agonist of Peroxisome Proliferator-Activated Receptor-γ (PPARγ) Recruits PPARγ-Coactivator-1α, Prevents Triglyceride Accumulation, and Potentiates Insulin Signaling in Vitro

Abstract: Partial agonists of peroxisome proliferator-activated receptor-gamma (PPARgamma), also termed selective PPARgamma modulators, are expected to uncouple insulin sensitization from triglyceride (TG) storage in patients with type 2 diabetes mellitus. These agents shall thus avoid adverse effects, such as body weight gain, exerted by full agonists such as thiazolidinediones. In this context, we describe the identification and characterization of the isoquinoline derivative PA-082, a prototype of a novel class of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 64 publications
(105 reference statements)
3
113
1
4
Order By: Relevance
“…A mammalian twohybrid assay using full-length cofactors showed that the coactivator SRC2 (TIF-2) interacts with rosiglitazonebound PPARg but not with F-L-Leu-bound PPARg, whereas both F-L-Leu and rosiglitazone have similar binding of SRC1 (Rocchi et al, 2001). These full-length data differ from peptide recruitment assay results that have demonstrated that SRC 1, 2, and 3 peptides are all less recruited to PPARg by F-L-Leu than by rosiglitazone (Rocchi et al, 2001;Burgermeister et al, 2006). The lack of SRC2 recruitment and the maintained SRC1 recruitment (compared with rosiglitazone) by F-L-Leubound PPARg may be at least partially responsible for the reduced weight gain in F-L-Leu-treated mice.…”
Section: B Peroxisome Proliferator-activated Receptor G Functioncontrasting
confidence: 65%
See 2 more Smart Citations
“…A mammalian twohybrid assay using full-length cofactors showed that the coactivator SRC2 (TIF-2) interacts with rosiglitazonebound PPARg but not with F-L-Leu-bound PPARg, whereas both F-L-Leu and rosiglitazone have similar binding of SRC1 (Rocchi et al, 2001). These full-length data differ from peptide recruitment assay results that have demonstrated that SRC 1, 2, and 3 peptides are all less recruited to PPARg by F-L-Leu than by rosiglitazone (Rocchi et al, 2001;Burgermeister et al, 2006). The lack of SRC2 recruitment and the maintained SRC1 recruitment (compared with rosiglitazone) by F-L-Leubound PPARg may be at least partially responsible for the reduced weight gain in F-L-Leu-treated mice.…”
Section: B Peroxisome Proliferator-activated Receptor G Functioncontrasting
confidence: 65%
“…However, both rosiglitazone and GW0072 recruited far less NCoR to PPARg compared with vehicle in a mammalian two-hybrid assay (Oberfield et al, 1999). Additionally, GW0072 recruited the PGC1a peptide to a similar degree as rosiglitazone, despite recruiting far fewer SRC1, SRC2, and SRC3 peptides (Burgermeister et al, 2006). Recruitment of PGC1a likely promotes insulin sensitization, as it is upregulated with exercise and likely contributes to some of the observed benefits of exercise on metabolic syndrome, so a strong case for the benefits of PGC1a can be made (Handschin and Spiegelman, 2008).…”
Section: B Peroxisome Proliferator-activated Receptor G Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…[54][55][56]. Our data suggest that PPARγ operates differently in normal and pathological tissues as a result of heterodimerization with distinct RXR isotypes.…”
Section: Discussionmentioning
confidence: 75%
“…Primers covering exon 3 and the 5 ¶-untranslated region of the human caveolin-1 gene were Cav1-S, 5 ¶-TTGGAAGGC-CAGCTTCAC-3 ¶, and Cav1-AS, 5 ¶-CTATCCTTGAAATGTCA-3 ¶ (23). The results were normalized against h 2 -microglobulin (21) and S12 ribosomal protein (22) as previously published.…”
Section: Methodsmentioning
confidence: 99%